SPATIAL-TEMPORAL EVOLUTION OF THE OCCUPATION LINE IN THE COASTAL ZONE IN THE PERIOD 2006-2023 IN THE MUNICIPALITY OF SÃO JOSÉ DA COROA GRANDE-PE WITH EMPHASIS ON THE CONSTRUCTION AREA - Marcelino da Silva, Marcone; das Neves Gregório, Maria; Cristina de Souza Matos Carneiro, Márcia; do Amaral Vaz Manso, Valdir; do Nascimento Souza, Alexandre (Journal of Interdisciplinary Debates, 2025)
This research aims to examine and compare the spatiotemporal evolution of the building line along the coastal zone of the municipality of São José da Coroa Grande during the periods of 2006, 2014, 2018, 2022, and 2023. Conducting temporal analyses makes it possible to identify trends and transformations that have shaped the coastal landscape of São José da Coroa Grande-PE over the years. The study was carried out through the analysis of satellite images from the selected years, using Geographic Information Systems (GIS) QGis and ArcGis 10.8. For the temporal analysis of the building line, the DSAS software was used in conjunction with ArcGis 10.8. Additionally, a topographic survey was conducted using GNSS-RTK CHCNAV equipment. The study area covers the municipality of São José da Coroa Grande, with approximately 9.9 km of shoreline, subdivided into three sectors (1, 2, and 3), defined according to the degree of urbanization, intensity of anthropic occupation, and coastal vulnerability. To monitor the temporal evolution of the building line, satellite images from the years 2006, 2014, 2018, and 2022, as well as UAV images collected in 2023, were used.In Sector 1, a significant advance of the building line was identified, with a maximum value of 101.00 m between 2006 and 2022, concentrated mainly in the northern portion of the sector. The highest average displacement occurred between 2006 and 2014 (4.19 m), reflecting intense urban expansion toward the beach strip. Sector 2 presented more moderate displacements, with a maximum value of 10.82 m and an average of 2.75 m for the period 2006–2014, as well as a trend toward stabilization in the following periods. This stability may be associated with spatial saturation or the reduction of anthropic pressure during the pandemic period. Sector 3 showed the greatest displacements between 2006 and 2014 (up to 13.49 m), but with the highest average recorded during the period 2006–2018 (2.70 m), especially in the southern portion of the sector, near Sector 2. This region showed more intense erosive processes, indicating environmental fragility. The study of the building line in the coastal zone of São José da Coroa Grande-PE revealed distinct patterns of urban occupation among the three analyzed sectors. The spatial behavior of the advance of the building line highlights the need for specific strategies for coastal urban management, taking into account unplanned growth and the impacts on the morphodynamics of the coastal zone.